An analogue of the Baum-Connes isomorphism for coactions of compact groups - Meyer, Ralf; Nest, Ryszard (Mathematica Scandinavica, 2007)
We formulate and prove the analogue of the Baum-Connes conjecture for coactions of connected compact groups.